Impact of transcatheter aortic valve implantation on the risk of mortality in patients with severe aortic valve diseases: a health insurance-based analysis. Issue 1 (21st April 2018) - Barth, Alexander; Yücel, Seyrani; Ince, Hüseyin; Doblhammer, Gabriele
Abstract : Background: Transcatheter aortic valve implantation (TAVI) is a minimally invasive treatment for aortic valve patients who are inoperable or have a prohibitively high surgical risk for surgical aortic valve replacement (SAVR). Most studies compare the efficacy of TAVI and SAVR, yet the assessment of TAVI for this group of patients requires more study. Methods: This quasiexperimental study compares TAVI cases (ages of 75–90 years, n=187) ex-post with a control group without implantation (n=728, 4:1 ratio intended). The control group was drawn randomly on the condition that it matches the TAVI cases based on age at aortic valve disease incidence, gender and comorbidity index. The mortality risk is analysed from incident diagnosis. Data were taken from three random samples of health claims data in Germany's largest public health insurance (Allgemeine Ortskrankenkassen) and cover the years 2004–2013 (n=750 000). Results: Compared with the medically treated control group with 6+ comorbidities, medically treated patients with fewer comorbidities have half the mortality risk (HR 0.48, 95% CI 0.34 to 0.69, p<0.001). TAVI patients with fewer than six comorbidities show a mortality risk half that (HR 0.23, 95% CI 0.09 to 0.63, p=0.004). TAVI patients with 6+ comorbidities do not benefit from TAVI compared with the control group with 6+ comorbidities (HR 0.99, 95% CI 0.71 to 1.36, p=0.93). Conclusion: TAVI is an effective therapy for aortic valve disease patients with few comorbidities; it is not effective for patients with a high comorbidity burden. Careful assessment of the individual patient in terms of comorbidities is important for a beneficial outcome.